POSITIONING AHL AL-BAYT WITHOUT TENDENCIES: AL-SHAWKANI'S CONTRIBUTION TO DETERMINING THE HADITH IN ISLAMIC SHARIA - Ahmad Azmi Ahsantu Dhonni; Muhid; Andris Nurita; Afif Maulana (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Shiites tend to prioritize Ahl al-Bayt's position in transmitting Hadith. It affects the determination of Hadith as a primary source in Islamic Sharia. The Zaydi Maddhab, the Shi'a branch, is very dominant in Yemen. However, al-Shawkani, educated by his father and his Zaydist teachers, has a different view from Zaydism in positioning Ahl al-Bayt. Al-Shawkani saw that the uncertain political conditions in Yemen and the rise of blind taqlid directed Muslims to go astray and heresy at that time. This study examines al-Shawkani's stance on Ahl al-Bayt's position in determining the basis of Sharia law through his relevant works. Therefore, this socio-historical investigation also reveals the contribution of al-Shawkani thought in Islamic studies. This research shows that although al-Shawkani was influenced by Zaydism, objectively, he did not prioritize Ahl al-Bayt and was not passionate about one particular madhhab—a stance often opposed by Yemen's Zaydist scholars. In his works, al-Shawkani indirectly agrees with the opinion of Sunni scholars in determining the narrators of the Hadith as the primary source for deciding Islamic Sharia law. Thus, the contribution of al-Shawkani, who positions Hadith narrators objectively and scientifically, both Ahl al-Bayt and non-Ahl al-Bayt, is set the same as the criteria most scholars of Hadith experts determined.